Chilling effect: how bad regulation killed comparative advertising in Peru - Rivera Serrano, Alfonso (2017)
This article provides a criticism of the Peruvian policy regulating comparative advertising.The first section of the article describes the evolution of the regulatory treatment of comparative advertising in Peru and explains the “chilling effect” caused by its current regulation. The second section introduces the concept of “chilling effect” used in decisions about freedom of speech, analyzes the constitutional protection of commercial speech as a manifestation of the freedom of speech, and describes the test developed in the United States and Spain to analyze restrictions to commercial speech. The third section applies the test to the regulation of comparative advertising in Peru and concludes that this regulation is unconstitutional.